Interpreting the Mark in the Graphic Novel "Palestine": A Reportage of the Palestinian-Israeli Conflict - Angga Priatna (2022)
The graphic novel "Palestine" is one of the graphic novel documentaries about the conflict in Palestine. The purpose of this research is to understand the process of meaning 'marks' in the graphic novel. The method used is qualitatively descriptive. The results suggest that the graphic novel "Palestine" may never know whether the "mark" can change things, but Joe Sacco's graphic novel "Palestine" was recognized as the best novel at the American Book Award in 1996, although at the same time it was denounced by the Israeli media and public.Ã‚Â